Integrated 60GHz RF Beamforming in CMOS - Yu, Yikun; Baltus, Peter G.M.; van Roermund, Arthur H.M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
The 60GHz band is promising for applications such as high-speed short-range wireless personal area network (WPAN), real time video streaming at rates of several Gbps, automotive radar, and mm-Wave imaging, since it provides a large amount of bandwidth that can freely (i.e. without a license) be used worldwide. However, transceivers at 60GHz pose several additional challenges over microwave transceivers. In addition to the circuit design challenges of implementing high performance 60GHz RF circuits in mainstream CMOS technology, the path loss at 60GHz is significantly higher than at microwave frequencies because of the smaller size of isotropic antennas. This can be overcome by using phased array technology. Integrated 60GHz RF Beamforming in CMOS describes new concepts and design techniques that can be used for 60GHz phased array systems. First, general trends and challenges in low-cost high data-rate 60GHz wireless system are studied, and the phased array technique is introduced to improve the system performance. Second, the system requirements of phase shifters are analyzed, and different phased array architectures are compared. Third, the design and implementation of 60GHz passive and active phase shifters in a CMOS technology are presented. Fourth, the integration of 60GHz phase shifters with other key building blocks such as low noise amplifiers and power amplifiers are described in detail. Finally, this book describes the integration of a 60GHz CMOS amplifier and an antenna in a printed circuit-board (PCB) package.
Keywords: Engineering; Microwaves; Systems engineering; Engineering; Circuits and Systems; Semiconductors; Microwaves, RF and Optical Engineering